Estrogenic and androgenic activity of PCBs, their chlorinated metabolites and other endocrine disruptors estimated with two in vitro yeast assays - Svobodová, Kateřina; Plačková, Martina; Novotná, Veronika; Cajthaml, Tomáš (Science of the total environment, 2009)
Investigations of environmental pollution by endocrine-disrupting chemicals are now in progress. Up to now, several in vitro bioassays have been developed for evaluation of the endocrine disruptive activity; however, there is still a lack of comparative studies of their sensitivity. In this work comparison of the estrogen screening assay based on beta-galactosidase expression and a bioluminescent estrogen screen revealed differences in the sensitivity and specificity of the two tests. With the beta-galactosidase screen a slight estrogen-like activity of Delor 103, a commercial mixture of PCB congeners, and a fungicide triclosan was measured whereas no activity was detected using the bioluminescent assay. A bioluminescent androgen test negated previously suggested androgenic potential of triclosan. Further, this work demonstrates the androgenic activity of Delor 103, with an EC(50) value of 2.29 x 10(-2)mg/L. On the other hand, chlorobenzoic acids (CBAs), representing potential PCB degradation metabolites, exhibited no androgenic activity but were slightly estrogenic. Their estrogenicity varied with their chemical structure, with 2,3-CBA, 2,3,6-CBA, 2,4,6-CBA and monochlorinated compounds exhibiting the highest activity. Thus the results indicated possible transitions of the hormonal activity of PCBs during bacterial degradation.
Keywords: Yeasts; Endocrine Disruptors; biotest; estrogeny; kvasinky; beta-Galactosidase; Estrogens; látky znečišťující životní prostředí; polychlorované bifenyly; Androgens; androgeny; Polychlorinated Biphenyls; endokrinní disruptory; Environmental Pollutants; Biological Assay; beta-galaktosidasa